2023
DOI: 10.1101/2023.01.05.522889
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generation of eco-friendly channel catfish,Ictalurus punctatus, harboring alligator cathelicidin gene with robust disease resistance by harnessing different CRISPR/Cas9-mediated systems

Abstract: The CRISPR/Cas9 platform holds promise for modifying fish traits of interest as a precise and versatile tool for genome manipulation. To reduce introgression of transgene and control reproduction, catfish species have been studied for upscaled disease resistance and intervening of reproduction to lower the potential environmental risks of introgression of escapees' as transgenic animals. Taking advantage of the CRISPR/Cas9-mediated system, we succeeded in integrating the cathelicidin gene from an alligator (Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Therefore, fish‐, AMG‐ and pathogen‐moderator analyses were performed mainly for these three parameters. Recently, Wang et al 34 demonstrated that different loci for transgene integration significantly affect survival after bacterial infection in cathelicidin‐ and cecropin‐transgenic channel catfish. As a result, we also conducted the locus‐moderator analysis to determine the effect of AMG integration loci on disease resistance enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, fish‐, AMG‐ and pathogen‐moderator analyses were performed mainly for these three parameters. Recently, Wang et al 34 demonstrated that different loci for transgene integration significantly affect survival after bacterial infection in cathelicidin‐ and cecropin‐transgenic channel catfish. As a result, we also conducted the locus‐moderator analysis to determine the effect of AMG integration loci on disease resistance enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…From the first AMG‐transgenic catfish, Dunham et al 25 concluded that cecropin can enhance CSR from 27% to 96% when channel catfish were infected with F. columnare , and a similarly positive result was also observed in medaka 39 . Additionally, survival improvements of over 30% were achieved in lactoferrin‐transgenic grass carp, lysozyme‐/hepcidin‐transgenic zebrafish, cecropin‐transgenic rainbow trout and cathelicidin‐transgenic channel catfish against various bacteria, respectively 26,27,29,34,53 . Regarding viruses, GCRV and IHNV were investigated in lactoferrin‐transgenic grass carp and cecropin‐/ CF‐17 ‐transgenic rainbow trout, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations